The Shift in Ideological Orientation of Muhammadiyah Youth as an Effort to Maintain Religious Harmony in Lamongan Regency - Rr. Kusuma Dwi Nur Ma’rifati (EDUJAVARE: International Journal of Educational Research, 2026)
This study examines the shift in ideological orientation among youth within Muhammadiyah in Lamongan Regency amid increasing exposure to diverse religious discourses and socio-cultural dynamics. The research aims to analyze the factors driving ideological transformation and its implications for maintaining religious harmony. Employing a qualitative descriptive-analytical approach, data were collected through in-depth interviews, participant observation, and document analysis involving selected Muhammadiyah youth cadres, and analyzed using an interactive model grounded in Rational Choice Theory. The findings reveal that ideological shifts occur in multidirectional patterns, ranging from more conservative scripturalist tendencies to more accommodative and culturally adaptive orientations. These transformations are influenced by higher education environments, transnational religious exposure, and local social interactions, while organizational affiliation remains stable due to rational considerations such as social capital and institutional attachment. The study concludes that such ideological flexibility does not necessarily weaken organizational cohesion but instead creates opportunities for fostering inclusive and dialogical religious practices that support social harmony. This research contributes to the development of a nuanced framework for understanding Islamic youth dynamics by emphasizing the interplay between individual agency, institutional context, and socio-cultural influences.